INTERPRETASI BENTUK BADAN USAHA MILIK DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Amelia Sri Kusuma Dewi; Ngesti D. Prasetyo (Jurnal Media Hukum, 2015)
This research aimed to analyze about Interpretation Forms village-owned enterprises According to Law No. 6 of 2014 About the Village. To answer the legal issues mentioned above, the type of research conducted by the researchers are using a normative juridical research, by using the approach the statute approach and conceptual approach. From the analysis of Law No. 6 of 2014 About the village and its implementing regulations, it was concluded that the establishment of village-owned enterprises, the Government does not impose the form of a particular enterprise, this is an effort to grow the rural economy naturally through a form of business entity characterized by village, Rule further that in terms of business activities can run and well developed, it was possible at the time village-owned enterprises follow legal entities established in the provisions of the legislation, here the researchers interpret of legislation, that the legal entity in question is Village Public Company. Additionally village-owned enterprises can consist of business units that are legal entities which may be institutions whose business is derived from its ownership village-owned enterprises and communities.